2018
DOI: 10.1002/ptr.6048
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol induces cytotoxicity in human cervical cancer cells but causes cisplatin resistance: Involvement of MEK–ERK activation

Abstract: Carvacrol has been shown to possess anticancer activity, but the mechanism is unknown, as well as the possibility of interaction with anticancer drugs. The aim of this study was to investigate the role of mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling in carvacrol-induced human cervical cancer HeLa cell cytotoxicity. In addition, we studied sensitization of HeLa cells to cisplatin (CP) by carvacrol. Both carvacrol and CP showed dose-dependent cytotoxicity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 43 publications
(44 reference statements)
1
32
0
Order By: Relevance
“…Many researches about chemotherapeutic drugs 41,42 , tumor-related gene 43 , microRNA 38 , and LncRNA 44 have shown multiple effects on cervical cancer by regulation of MAPK signaling pathway. However, most of the studies agreed that phosphorylation of ERK 38,45 was upregulated to promote the proliferation or (and) suppress the apoptosis 33,46 of cervical cancer, while evidences showed contrary effect in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researches about chemotherapeutic drugs 41,42 , tumor-related gene 43 , microRNA 38 , and LncRNA 44 have shown multiple effects on cervical cancer by regulation of MAPK signaling pathway. However, most of the studies agreed that phosphorylation of ERK 38,45 was upregulated to promote the proliferation or (and) suppress the apoptosis 33,46 of cervical cancer, while evidences showed contrary effect in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we thought ERK cannot regulate tumorigenesis directly. Previous studies demonstrated that activation of ERK MAPK could also induce cytotoxicity or tumor inhibition in some cancers 19,41,47 . Some studies revealed that activation of ERK could promote apoptosis progress 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to unveil the significant outcomes of isoprenoid-based manipulations of the mevalonate pathway and HMGCR in cancer cells. γ-Tocotrienol at 0–30 μM downregulated HMGCR, membrane H-, K-, and N-Ras, and Raf-1, p-AKT, and p-ERK in HL-60 cells (Chen et al, 2015), adding to a long list of in vitro and in vivo studies showing isoprenoid-mediated suppression of the growth of cancer cells including those of blood (Shoff et al, 1991; Melnykovych et al, 1992; Mo and Elson, 1999; Lee et al, 2015), breast (Iqbal et al, 2004; Pierpaoli et al, 2010, 2013; Gomide et al, 2013; Ding et al, 2017), cervix (Yazlovitskaya and Melnykovych, 1995; Xu et al, 2017; Potocnjak et al, 2018), colon (Mo and Elson, 1999; Gomide et al, 2013, 2016), liver (Wada et al, 2005; Crespo et al, 2013; Scolastici et al, 2014; Rodenak-Kladniew et al, 2018), lung (Mo and Elson, 1999; Wada et al, 2005; Gomide et al, 2013; Galle et al, 2014), mouth (Liang et al, 2013; Madankumar et al, 2013), pancreas (Hussein and Mo, 2009; Fernandes et al, 2013), prostate (Mo and Elson, 2004; Sundin et al, 2012; Fernandes et al, 2013; Jones et al, 2013; Yeganehjoo et al, 2017), skin (Mo et al, 2000; McAnally et al, 2007; Chang et al, 2009; Chaudhary et al, 2013), and stomach (Dong et al, 2013; Liu et al, 2013). Concomitantly, isoprenoids induce cell cycle arrest and apoptosis in the tumor cells (Mo and Elson, 1999, 2004; Dong et al, 2013; Jones et al, 2013; Yeganehjoo et al, 2017; Rodenak-Kladniew et al, 2018; Sailo et al, 2018).…”
Section: Isoprenoids and Their Mechanisms Of Actionmentioning
confidence: 99%
“…Studies have shown that carvacrol is effective against Salmonella and Escherichia coli, Campylobacter jejuni and Listeria monocytogenes (Obaidat and Frank, 2009;Van et al, 2012;Upadhyay et al, 2012). Salmonella colonies on celery were destroyed by carvacrol (Ravishankar et al, 2010). Candida albicans taken from patients using dentures were tested against carvacrol.…”
Section: Effects Of Carvacrol and Carvacrolmentioning
confidence: 99%